Pembinaan Keagamaan Terpadu di Kelurahan Tamangapa Kecamatan Manggala Kota Makassar - Farida Aprianti Lagalanti (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
KKN V STIBA Makassar is a form of community service which is one of the pillars of the Tridarma Perguruan Tinggi. The method of implementing the service program begins with mapping the problems and needs of the community using SOAR analysis. After the analysis is done, a work program that is appropriate and needed by the community is drawn up. Work programs that have been successfully implemented include: Al-Qur'an Education Program including DIROSA, TPA Teaching, Tahfizh and Al-Qur'an Memorization Programs; The Community Development Program includes Ramadan Special Taklim activities and Arabic Language Learning; The Training Program includes Provision of Body Organizing; The Community Service Program includes Ramadhan Sharing, Mask Sharing, Mukena Sharing and Blessing Friday. The enthusiasm of all activity participants, both children and teenagers, even mothers, was seen in all the programs that were followed. All programs are running well and have shown results that are in accordance with the KKN objectives that have been proclaimed, namely the development of Islamic knowledge, increasing skills in reading the Qur'an and Arabic as well as increasing community skills.